«АЛПОМИШ» ДОСТОНИ ОБРАЗЛАРИ ТАВСИФИ - Алламбергенова, Н. (SCIENCE and SOCIETY, 2016)
The works known as “Alpomish” (among Uzbeks), “Alpamis” (among Karakalpaks), “Alpamis batir” (among Kazakhs), “Alp Manash” (among Kazan Tatars), “Alpamish va Barsin Hillu” (among Bashkirs) have been in the focus of attention of folklorists for a century among the Turkic peoples. The epos expresses the past, present and future of the Turkic peoples. The article deals with the study of the epic poem “Alpamish” which is a valuable manuscript of the Turkic peoples and are discribed the main characters of the epos.
Keywords: folklore and folkloristics; epic poem; hero; bakhshi; main character; variant; variation